Supporting Low-Latency Applications through Hybrid Cost-Optimised Cloudlet Placement - Mondal, Sourav; Das, Goutam; Wong, Elaine (Proceedings / International Conference on Transparent Optical Networks, 2018)
Low-latency applications such as augmented reality, cognitive assistance, and context-aware computation are better supported by augmenting cloud networks with cloudlet enabled edge computing solution. This overcomes the high-transmission latency arising from the edge devices in the access segment to cloud servers located in the core. In this talk, we will review our recently proposed hybrid cost-optimization framework for optimal cloudlet placement over existing passive optical access networks, subject to capacity and latency constraints. In our work, we formulate a mixed-integer non-linear program to identify ideal locations (either at the central office (CO), remote node (RN), or in the field) for cloudlet placement over three deployment areas of differing population densities. Our results point to the fact that the installation of more RN and CO-located cloudlets will yield an improved cost optimal solution than the installation of field cloudlets alone, and that the percentage of the incremental energy budget arising from the installation of cloudlets are low.